Efforts to Improve the Ability to Run 100 Meter Sprints with the Green-Black Playing Method for Class X-8 Students of SMA Negeri 7 Malang: Penelitian - Agianto, Mario Bagus Ramadhan; Heynoek, Febrita Paulina; Sunarko, Sunarko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve the learning of 100-meter sprint run for students of class X-8 SMAN 7 Malang through Green-Black game. The method used is Classroom Action Research (PTK) which consists of three stages: pre-cycle, cycle I, and cycle II. In the pre-cycle stage, only 9 out of 34 students (26.47%) reached the target sprint time, while 25 students (73.53%) were not complete. After treatment in cycle I, completeness increased but did not reach 75%, so it was continued to cycle II. In cycle II, 27 students (79.41%) achieved mastery, showing a significant improvement from the pre-cycle. Thus, the Green-Black game proved to be effective in improving students' ability to run the 100-meter sprint. These results show that a game-based learning approach can motivate students, the total increase in completeness from pre-cycle to cycle II is 52.94%. Based on these results, no further cycles are needed because the completeness has exceeded the minimum limit of 75%.